Linking drug and food addiction: an overview of the shared neural circuits and behavioral phenotype - Passeri, Alice; Municchi, Diana; Cavalieri, Giulia; Babicola, Lucy; Ventura, Rossella; Di Segni, Matteo (Frontiers in Behavioral Neuroscience, 2023)
Despite a lack of agreement on its definiGon and inclusion as a specific diagnosable disturbance, the Food AddicGon construct is supported by several neurobiological and behavioral clinical and preclinical findings. Recognizing Food AddicGon is criGcal to understanding how and why it manifests. In this overview, we focused on: 1. the hyper-palatable food effects in Food AddicGon development; 2. specific brain regions involved in both food and drug addicGon; and 3. animal models highlighGng commonaliGes between Substance Use Disorders and Food AddicGon. Although results collected through animal studies emerged from protocols differing in several ways, they clearly highlight commonaliGes in behavioral manifestaGons and neurobiological alteraGons between Substance Use Disorders and Food AddicGon characterisGcs. To develop improved Food AddicGon models, this heterogeneity should be acknowledged and embraced so that research can systemaGcally invesGgate the role of specific variables in the development of the different behavioral features of addicGon-like behavior in preclinical models.